Effective evacuation problem by pedestrian allocation and vehicle dispatching - Yan, Mengyuan (Nanyang Technological University, 2024)
Many unforeseen events such as natural disasters and urban emergencies can pose threats to residents’ lives and property. To ensure individuals’ safety and the well-being of communities, it is necessary to solve the emergency evacuation problem, i.e., to transport the maximum number of evacuees from the affected areas to the safety shelters in the shortest possible time. Many past studies have been conducted from two aspects: location strategies and dispatching rules. With the development of technology, real-time information about the affected areas can be available to the evacuation system, and the evacuation system is required to make optimal control decisions in conjunction with real-time information, which has not been prominently addressed in past research. In this project, controllers (CRH, tCRH, sCRH) based on the idea of RHC (Receding Horizon Control) are applied in emergency evacuation scenarios to solve the vehicle dispatching and allocation problem in conjunction with real-time information, and their characteristics are compared and analyzed with the help of simulations in MATLAB. The simulation results indicate that the sCRH controller outperforms other controllers in the Euclidean case. However, considering the road constraints in the real-world scenario and the computational complexity, the CRH controller proves to be able to solve the effective evacuation problem.